Dimensi Eskatologis Surah Al-Mulk Analisis Ayat-Ayat tentang Siksa Kubur dalam Tafsir Al-Misbah - Syaifudin; Norzimah Kasran (Kartika: Jurnal Studi Keislaman, 2025)
This study examines the eschatological dimension of Surah al-Mulk in Tafsir al-Misbah by M. Quraish Shihab, focusing on the concept of grave punishment as an integral part of Islamic teachings about life after death. The research employs a qualitative method with a thematic (maudhu‘i) tafsir approach, analyzing verses of Surah al-Mulk related to the themes of life, death, and divine retribution for disbelievers. The findings reveal that Surah al-Mulk emphasizes life and death as tests of faith (verse 2), describes the torment prepared for those who deny the truth (verses 6–9), and highlights the importance of intellect and hearing as means of spiritual salvation (verse 10). According to Quraish Shihab, these verses serve as moral and spiritual reminders of the consequences of human deeds in the barzakh realm. Theologically, Surah al-Mulk affirms Allah’s justice and mercy, while educationally it encourages humans to live reflectively, faithfully, and responsibly in preparation for both worldly and eternal life